Mauvais goût ou goût moderne ? Controverses autour du rococo - Katalin Bartha-Kovács (Svět Literatury, 2022)
The aim of this study is to examine the controversies surrounding the artistic movement known a posteriori as rococo. Firstly, the debates about the term “rococo” as a category of style will be presented. Using the example of contemporary judgements on the art of Jean-Antoine Watteau (1684–1721), we will then show how the amateurs and critics of his time perceived the painter’s work. Called the “modern style” or the “picturesque genre”, later qualified as “bad taste”, this eminently decorative trend, the rococo, provoked very different reactions in the 18th century, oscillating between appreciation and condemnation.